PENGARUH LEADER MEMBER EXCHANGE (LMX), KEPUASAN DAN KELELAHAN KERJA TERHADAP KINERJA POLISI WANITA DI POLDA SULAWESI TENGGARA - Ribka Diana Linsay Siwi; La Hatani La Hatani; La Ode Asfahyadin Aliddin (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2023)
The purpose of this study was to examine and explain the effect of LMX, job satisfaction, and work exhaustion on the performance of policewomen at Polda Sultra either simultaneously or partially. The paradigm of this study is positivist with a quantitative approach. Data were collected in a cross-sectional manner using a one-line questionnaire with the link: https://bit.ly/angket-riset-Ribka-Diana.  The sample of this research is allpolicewomenn in Polda Sultra as many as 63 people. The analytical tool used is Multivariate Regression Analysis.The results showed that LMX, satisfaction, and work exhaustion had a positive and significant effect on policewoman performance together. Furthermore, the partial test results of LMX proved to have a positive and significant effect on policewoman performance. Then job satisfaction has a positive and significant effect on policewoman performance. Work exhaustion has also been shown to have a negative and significant effect on policewoman performance. This means that the better the application of LMX and job satisfaction as well as a significant decrease in work exhaustion, the policewoman performance increases significantly. This result is also reinforced by respondents' statements based on the LMX description, job satisfaction, and policewoman performance, the majority of respondents stated that the implementation was good at the Southeast Sulawesi Regional Police.